Maternal depression as a mediator of preterm birth and child development - Ashish KC; Miriam Sophia Meier; Jaya Chandna; Lea Kreyenbaum; Carin Andrews; Omkar Basnet (Developmental Medicine & Child Neurology, 2026)
Abstract Aim To assess the causal pathway between preterm birth and infant neurodevelopmental delay, with maternal depression as the mediator using a counterfactual mediation framework. Method A prospective cohort of 1253 mother–infant pairs were enrolled and followed up until 6 months in Nepal. Preterm birth was assessed using medical birth register; maternal depression and infant neurodevelopmental delay were assessed using maternal interview. Causal mediation analysis was performed using logistic regression models using the R mediation package, estimating average causal mediation effect (ACME), average direct effect, total effect, and proportion mediated. Model diagnostics included multicollinearity, goodness‐of‐fit, influential observations, and positivity. Results Preterm birth was associated with increased odds of infant neurodevelopmental delay (total effect odds ratio [OR] = 1.12, 95% confidence interval [CI]: 1.06, 1.18). Maternal depression symptoms partially mediated this association (ACME OR = 1.04, 95% CI: 1.02, 1.07), with a direct effect of preterm birth remaining significant (average direct effect OR = 1.07, 95% CI: 1.02, 1.13). Approximately 38% of the total effect was mediated by persistent maternal depression. Sensitivity analyses indicated moderate robustness to unmeasured confounding. Interpretation Maternal depression is an important pathway linking preterm birth to infant neurodevelopmental delay, though additional direct mechanisms exist. Interventions targeting maternal mental health may partially mitigate the developmental risks associated with preterm birth.